1937
DOI: 10.1103/physrev.52.390
|View full text |Cite
|
Sign up to set email alerts
|

The Disintegration of Lithium by Deuterons

Abstract: It is true that the neutrino manifests itself in connection with particle energies far below those concerned in cosmic-rays, energies comparable with a million electron volts. It is to be observed, however, that there is nothing to require that / should change monotonically with increase of the velocity of the particle.It must further be pointed out that there is little to necessitate regarding the ordinary expression (3) as having anything to do with the quantity which we speak of in energy transitions in ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1939
1939
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…However, this state has been well established as a resonance in the n-a scattering cross section, 5 -6 and as peaks in the spectra from at least ten different reactions, the one most frequently investigated being Li 7 (d,a)He 5 . [7][8][9][10][11][12][13][14][15] Moreover, the anisotropy of the particles emitted in the decay of the ground state has been observed by several people, and supports an assignment of P3/2 to this state. (A P1/2 assignment requires an isotropic distribution of the particles resulting from the disintegration of He 5 .)…”
Section: Introductionmentioning
confidence: 89%
“…However, this state has been well established as a resonance in the n-a scattering cross section, 5 -6 and as peaks in the spectra from at least ten different reactions, the one most frequently investigated being Li 7 (d,a)He 5 . [7][8][9][10][11][12][13][14][15] Moreover, the anisotropy of the particles emitted in the decay of the ground state has been observed by several people, and supports an assignment of P3/2 to this state. (A P1/2 assignment requires an isotropic distribution of the particles resulting from the disintegration of He 5 .)…”
Section: Introductionmentioning
confidence: 89%
“…Its presence was indicated by a study by Williams et al (1937) of the alpha-particle spectrum from the reaction They found a continuous distribution with a superposed peak which they ascribed to the reaction…”
Section: )mentioning
confidence: 95%
“…Further investigations of the reactions of neutrons and protons with tritium (TaSehek et al 1949, Argo et al 1950, however, provided evidence for an excited state at 21.6 ~ev. Downloaded by [UQ Library] at 13:08 03 February 2015 I:[eydenburg* 1941Keitler* 1947Freier* 1949Bradeu 1951, 1.q53 Putnam 1952Kreger* 1952, Atkins 1952Wickersham 1954, 1957Cork* 1954Freemantle* 1954' Williams* 1955Teem* I955 Eisberg 1956Brockman 1956Putnam* 1956a,b Vanecian 1956Chamberlain* 1956Miller* I957 Brussel* 1957Tyren* 1957 S.C. This work was not confirmed by later studies of proton-helium scattering in which the scattered protons were analysed to see if any of them had less energy than would be expected from an elastic collision.…”
Section: Pcmentioning
confidence: 99%
“…2 This resonance raises the ratio of the forward scattering cross sections of helium and hydrogen from 1.4 to 2.5 Mev to about 9 at 1 Mev. We have investigated the resonance scattering more closely by using a continuous neutron spectrum.…”
Section: Resonance Scattering Of Neutrons In Heliummentioning
confidence: 99%
“…2 Further experiments are indicated, such as simultaneous observations of dark current and fluorescence.…”
Section: Observations On the Dark Current Of A Willemite Crystalmentioning
confidence: 99%